Konstruksi Rak Penataan Gelas Air Minum Menggunakan Hasil Deformasi Benda-Benda Geometri dan Kurva Bezier - Hikmah Ardiantika Sari; Bagus Juliyanto; Firdaus Ubaidillah (jcgant, 2021)
Drinking water glass shelves are used as containers that can hold drinking water with a growing model. Drinking water glass shelves is made using thecniques which produced from deformation of geometric objects and Bezier curves. This research aims to made produces procedures for designing buffers, main shelves and more varied reliefs with one axis and three modeling axes. This research method divided into several stages. First, construct some basic objects as constituent components of drinking water glass shelves from deformation of octagonal, tube, beams, and the ball. Second, set some basic objects of the component of drinking water glass shelves two types of modeling axis. Third, arrange program using Maple 13. The results of this research obtained the procedure for designing various forms of constituent components of drinking water glass shelves from the basic object of a octagonal, tube, beams, and the ball. Furthermore, the procedure for assembling the components of drinking water glass from the first procedure result on two types of modeling axis.